Formative research for the development of a theory-based social behavior change communication plan for the More Milk in Tanzania (MoreMilkIT) project - Kelly, J. (Emory University, 2018)
Malnutrition is a problem throughout the world, disproportionately affecting impoverished, rural, and vulnerable populations.1 Tanzania is not spared the effects of malnutrition, as almost 90% of the population is located in rural regions2 and 30% of the population is classified as food insecure.3,4 Rural Tanzania relies heavily on livestock for nutritional and economic security.5 Research suggests that livestock keeping in East Africa holds potential for economic growth,6 that can be environmentally and culturally sensitive,7 with specific benefits to highly vulnerable populations such as women and children.8 The More Milk in Tanzania project seeks to use advanced value-chain development to improve livelihoods through focused livestock and dairy production and sale.9 This research was conducted as the formative research for a social behavior change communication (SBCC) plan to supplement the More Milk project implementation, specifically to improve maternal and child nutrition through animal sourced foods. Formative research was grounded in a combination of three theoretical frameworks, the COM-B model10 the Theoretical Domains Framework,11 and the Designing for Behavior Change methodology of a barrier analysis.12 The formative research was conducted in Masatu, Tanzania in the district of Handeni. A mixed-methods barrier analysis consisted of 51 doer/non-doer surveys, nine key informant interviews, and four focus groups. Doer/non-doer surveys measured characteristics and behavioral domains of mothers who did and did not complete selected behaviors. Behaviors of interest included those recommended by the WHO for adequate maternal nutrition for fetal development and infant and young child feeding practices.13-21 Qualitative data collection consisted of conversation about community issues, program participation, community eating habits, and perceptions of the selected maternal and child nutrition behaviors. Several key determinants of behavior were identified including, access to resources, such as time, money, and food, socially normalized support from important family members, such as husbands and older female relatives, and both perceived positive/negative consequences and barriers/facilitators to maternal and child nutrition behaviors. Major themes such as perceived insufficient milk and consumption discrepancies between pregnant and lactating women and infants and children also arose. Using these results, this research lays the groundwork for a theory-based SBCC plan to improve maternal and child nutrition.